PRICE EARNING RATIO PADA PERUSAHAAN GO PUBLIK INDONESIA - Teguh Gunawan Setyabudi; Susanti; Dian Palupi; Ulfah Setia Iswara (Jurnal Ekonomi Dan Bisnis, 2026)
This study aims to examine the determinants of a company's Price to Earnings Ratio. This research is a quantitative descriptive study utilizing secondary data in the form of annual financial reports of publicly listed non-financial companies in Indonesia, obtained through the Indonesia Stock Exchange. The study was conducted on publicly listed companies in Indonesia. Data analysis was performed using multiple linear regression analysis. The results indicate that Return on Equity and Debt to Equity influence the Price-to-Earnings Ratio. Good company financial performance will send a positive signal to the capital market, leading to an increase in the company's stock.